IMPLEMENTASI KEBIJAKAN PENINGKATAN PRESTASI ATLET PUSAT PEMBINAAN DAN LATIHAN PELAJAR DAERAH (PPLPD) DINAS DAN OLAHRAGA DAERAH PROPINSI SULAWESI TENGAH - Erni, Erni (Katalogis, 2017)
The purpose of this study was to determine and analyze the Athletes Performance Improvement Policy Implementation and Training Development Center Regional Student (PPLPD) and the Regional Sports Office of Central Sulawesi Province. The main theory as a reference in this research is the theory of policy implementation that includes Edward III; (1) communication, (2) resources, (3) the disposition, (4) a bureaucratic structure. The research method using descriptive qualitative approach. The research location is housed at the Center for Student Development and Training Area (PPLPD) and the Office of the Provincial Sports Central Sulawesi with an informant as much as 5 people were selected purposively. The data collection was done by interviewing, observation, and documentation. Analysis using Interactive model of Miles and Huberman. Based on the results of research, policy implementation Improved Performance Athlete Development Center and Training Student Area (PPLPD) Department and the Regional Sports Central Sulawesi province when viewed from the aspect (1) communication, (2) resources, (3) disposition, and (4) the structure of the bureaucracy , indicating that it is not effective, because there are still aspects that have not been run, namely communication, resources and disposition, bureaucratic structure goes well, just need to be improved in order to carve the highest performance and won the gold medal at events nationally and internationally in the future will come as expectations that can boast of athletes, officials and governments PPLPD Central Sulawesi.